Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 12 - Section 12.1 - The Algebra of Functions - Exercise Set - Page 842: 11


$(g\circ f)(-1)=-18$

Work Step by Step

$f(x)=x^{2}-6x+2;$ $g(x)=-2x$ $(g\circ f)(-1)$ First, find $f(-1)$ by substituting $x$ by $-1$ in $f(x)$: $f(-1)=(-1)^{2}-6(-1)+2=1+6+2=9$ Find $(g\circ f)(-1)$ by substituting $x$ by $9$ in $g(x)$: $(g\circ f)(-1)=g(9)=-2(9)=-18$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.